Fire and grazing in the Caldenal of Argentina: Effects on plant and soil carbon and nitrogen - Harris, Wylie N. (2007)
Fire and grazing can modulate feedbacks between pools of carbon and nitrogen of plant and soil, altering cycles of these elements in grassland ecosystems. The magnitude of these effects may be limited by climate and by limited plasticity in tissue chemistry within a given photosynthetic pathway. We tested the hypotheses that (1) fire reduces rates of C and N cycling, while grazing increases them, and (2) these changes are due to intraspecific changes in plant tissue chemistry rather than competitive replacements by species with differing tissue chemistry. Plant and soil C and N content and isotopic ratios, soil microbial biomass C, and potential C mineralization were measured in areas of the southern Caldenal region of central Argentina with known histories of fire and grazing. Results support the hypothesis that fire reduces rates of N cycling via intraspecific increases in plant tissue C/N. Contrary to our first hypothesis, grazing also reduced plant tissue N. Fire and grazing effects on plant tissue chemistry resulted primarily from changes in dynamics of soil inorganic N. These changes were due to intraspecific changes in plant tissue chemistry, which was in agreement with our second hypothesis. Potential C mineralization experiments revealed little difference between treatments in pool sizes and mean residence times of labile soil organic carbon. Livestock grazing and fire have significant influences on soil N dynamics, particularly as mediated by soil microbes, in managed grasslands of the southern Caldenal in Argentina